2010
DOI: 10.1007/s10344-010-0393-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of space and habitat use by northern bobwhites in South Florida, USA

Abstract: The manner by which animals use space and select resources can have important management consequences. We studied patterns of habitat selection by northern bobwhites (Colinus virginianus) on Babcock-Webb Wildlife Management Area, Charlotte County, Florida and evaluated factors influencing the sizes of their home ranges. A total of 1,245 radio-tagged bobwhites were monitored for 19,467 radio days during 2002-2007. The mean (±1 SE) annual home range size, estimated using the Kernel density method, was 88.43 (±6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
1
16
1
Order By: Relevance
“…In all comparisons, as multiple observations of the same bird could be temporally autocorrelated, we fitted generalized linear mixed models (Zuur et al ., ) with Gaussian‐distributed random errors to partition variation attributable to individual birds. Then, to test for the combined effect of all variables, we tested simultaneously for all main and two‐way interaction effects (Slade, Russell & Doonan, ; Moyer, McCown & Oli, ; Singh et al ., ). We removed nonsignificant ( α = 0.05) interaction terms sequentially such that the least significant interaction term was removed at each step.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In all comparisons, as multiple observations of the same bird could be temporally autocorrelated, we fitted generalized linear mixed models (Zuur et al ., ) with Gaussian‐distributed random errors to partition variation attributable to individual birds. Then, to test for the combined effect of all variables, we tested simultaneously for all main and two‐way interaction effects (Slade, Russell & Doonan, ; Moyer, McCown & Oli, ; Singh et al ., ). We removed nonsignificant ( α = 0.05) interaction terms sequentially such that the least significant interaction term was removed at each step.…”
Section: Methodsmentioning
confidence: 97%
“…We removed nonsignificant ( α = 0.05) interaction terms sequentially such that the least significant interaction term was removed at each step. We sequentially refit models until only significant interaction effects and all main effects remained in the model (Slade et al ., ; Moyer et al ., ; Singh et al ., ). Significant interaction effects were further explored using least squares means (i.e.…”
Section: Methodsmentioning
confidence: 97%
“…Indeed, the primary goal of planting food strips was to provide bobwhites with a supplemental food source during winter, season during which they do not reproduce. In addition, food strips affect positively home-range size and habitat (including nest site) selection by bobwhites in the BW area (Singh et al 2010), which justifies the continued use of those food strips.…”
Section: Effect Of Management Activities and Weather Conditionsmentioning
confidence: 99%
“…The most significant plant communities included dry prairie (9,737 ha), pine-palmetto (9,145 ha), and wet prairie (7,047 ha). A detailed description of the native vegetation on our study site can be found in Frye (1954) and Singh et al (2010). The area is subject to periodic short-duration flooding and prolonged drought that likely affect bobwhite habitat selection and demography.…”
Section: Species and Study Sitementioning
confidence: 99%
“…Bobwhite habitat use and demographic parameters are well documented in most agroecosystems, but information is lacking for subtropical pasturelands in the Southeastern USA (Singh et al 2011). However, Flanders et al (2006) and Kuvlesky et al (2002) described the negative impacts of exotic grasses on bobwhites in the Southwest.…”
Section: Introductionmentioning
confidence: 99%